Nilai-nilai Pendidikan Anti Korupsi di Sekolah Dasar Swasta Melati Kota Medan - Sari Ramadani (Adabiyah Islamic Journal, 2023)
Foundation located on Jl. Sumbawa II No.223 Marelan Indah Complex, Rengas Pulau village, Medan Marelan district. Melati Private Elementary School has interesting things related to how to implement anti-corruption educational values as stated in the school's vision and mission to realize students who are devout and have noble personalities so that later from here all students have an anti-corruption attitude imprinted in themselves. This study aims to explain how to implement anti-corruption educational values in students in schools. In addition, this study uses qualitative methods with Crasswell's realist ethnographic approach. Data collection techniques in this study also used participant observation techniques, in-depth interviews, and documentation. The result of this study is an honesty canteen program as a manifestation of the values of anti-corruption education at SD Swasta Melati Kota Medan by forming an anti-corruption indicator in schools, namely always speaking and doing according to facts (consistent), not doing fraudulent acts, not lying, and not recognizing other people's property as their own. Keywords: Education, Anti-corruption, Values of honesty